Formation of fine particles using supercritical fluid (SCF) process: Short review - Chafidz, Achmad; Jauhary, Thonthowy; Kaavessina, Mujtahid; Sumarno, Sumarno; Latief, Fahamsyah H. (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2018)
This paper will discuss about the utilization of supercritical fluid (SCF) process to produce fine particles. Supercritical fluids (SCFs) process can be considered as an emerging “clean” technology for the production of small-size or fine particles (e.g. micron-size). Microsphere is a material in micron scale which has been widely used as adsorbent, catalyst support, and drug delivery system. For advanced application, those materials are formulated in the form of porous microspheres. There are several methods that can be used using SCFs. Those method are, Rapid Expansion of Supercritical Solution (RESS), Gas Anti-Solvent/Supercritical Anti-Solvent (GAS/ SAS), Aerosol Solvent Extraction System (ASES), dan Solution Enhanced Dispersion by Supercritical Fluids (SEDS) and Particle from Gas-Saturated Solutions/Suspensions (PGSS). Considering the morphology of material which will be used to prepare microsphere, each of methods above has specific advantages and disadvantages toward the material. Based on the literatures, the ASES method is more likely to produce porous microparticles (microspheres). In the ASES method, porous microsphere formation is the result of interactions between: degrees of supersaturation, nucleation velocity and crystal growth.